Stool Xpert MTB/RIF as a possible diagnostic alternative to sputum in Africa: a systematic review and meta-analysis - Segala, Francesco Vladimiro; Papagni, Roberta; Cotugno, Sergio; De Vita, Elda; Susini, Maria Chiara; Filippi, Valeria; Tulone, Ottavia; Facci, Enzo; Lattanzio, Rossana; Marotta, Claudia; Manenti, Fabio; Bavaro, Davide Fiore; et al. (Frontiers in Public Health, 2023)
Introduction: Worldwide, COVID-19 pandemic lead to a large fall in the number of newly reported TB cases. In sub-Saharan Africa, microbiological diagnosis of TB is generally based on smear microscopy and Xpert MTB/RIF on sputum samples, but good quality sputum samples are often difficult to obtain, leading clinicians to rely on more invasive procedures for diagnosis. Aim of this study was to investigate pooled sensitivity and specificity of Xpert MTB/RIF on stool samples compared to respiratory microbiological reference standards in African countries. Methods: Four investigators independently searched PubMed, SCOPUS, and Web of Science until 12th October 2022, then screened titles and abstracts of all potentially eligible articles. The authors applied the eligibility criteria, considered the full texts. All the studies reported the data regarding true positive (TP), true negative (TN), false positive (FP) and false negative (FN). Risk of bias and applicability concerns were assessed with the Quadas-2 tool. Results: Overall, among 130 papers initially screened, we evaluated 47 works, finally including 13 papers for a total of 2,352 participants, mainly children. The mean percentage of females was 49.6%, whilst the mean percentage of patients reporting HIV was 27.7%. Pooled sensitivity for Xpert MTB/RIF assay for detecting pulmonary tuberculosis was 68.2% (95%CI: 61.1-74.7%) even if characterized by a high heterogeneity (I2=53.7%) (Figure 2). Specificity was almost 100% (99%, 95%CI: 97-100%; I2=45.7%). When divided for reference standard, in the six studies using sputum and nasogastric aspirate the accuracy was optimal (AUC=0.99, SE=0.02),whilst in the studies using only sputum for tuberculosis detection the AUC was 0.85 (with a SE=0.16). The most common source of bias was exclusion of enrolled patients in the analysis. Conclusions: Our study confirms that, in Africa, stool Xpert MTB/RIF may be a useful rule-in test for children above and below 5 years of age under evaluation for pulmonary tuberculosis. Sensitivity increased substantially when using both sputum and nasogastric aspirate as reference samples.